(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
The study examined capacity building and school factors as correlates of teacher productivity in public primary schools in Ondo State, Nigeria. The study investigated the relationship between participation in capacity building and Teacher productivity. It also investigated the relationship between school factors such as infrastructural facilities, instructional supervision and teacher productivity. The descriptive research of the survey type was used in the study. The population consisted of all Headteachers and class teachers of public primary schools in Ondo State. The sample for the study was 50 Headteachers and 400 class teachers. The sampling Techniques used was proportional stratified, purposive, and simple random sampling Techniques. Two self-designed instruments were used to collect relevant data from the subjects. They are capacity building and school factors questionnaire (CBASFQ) and Teacher productivity questionnaire. (TPQ). The face and content validity of the instruments was ensured while repairability coefficient of 0.86 was obtained for CBASFQ and 0.82 For TPQ. The data collected was analysed using both descriptive and inferential statistics. All hypothesis raised were tested at 0.05 level of significance. The study revealed that the level of Teacher productivity in public primary schools in Ondo State was moderate. The study also revealed that level of Teacher participation in capacity building was moderate. The study found out that participation in capacity building significantly influence teachers productivity.it was revealed that there was a significant relationship between infrastructural facilities, instructional supervision and teacher productivity. Based on the findings, it was recommended that seminars, workshops, conferences should be organized regularly for teachers and Headteachers in order to keep them abreast of current pedagogical practices and improve their Productivity. It was also recommended that the government should ensure adequate provision of infrastructural facilities such as classrooms, computers, electricity, furniture and fittings instructional materials to enhance Teacher productivity. Seminars and conferences should be organized for school heads to improve their supervisory role.